Critica, capitale e totalità - Finelli, Roberto (L'ospite ingrato, 2021)
Starting from a consideration of the relation between criticism and totality promoted by Hegel, the article proposes arguments for a Real Abstraction Marxism instead of a Marxism more traditionally bound to the idea of Contradiction. The aim is to show the modality of constitution of the daily mass general intellect, more open to fragmentation than unification.